Crossroads of the World (C.P. Johnston Co.)
Century 21 Exposition's Crossroads of the World at the center of America's Space Age World's Fair. Colorful international programs, sparkling entertainment and guests from around the world featured here daily. Boulevards of the World lead to this hub of excitement.